Diverging phenological responses of Arctic seabirds to an earlier spring. (28th August 2019) - Descamps, Sébastien; Ramírez, Francisco; Benjaminsen, Sigurd; Anker‐Nilssen, Tycho; Barrett, Robert T.; Burr, Zofia; Christensen‐Dalsgaard, Signe; Erikstad, Kjell‐Einar; Irons, David B.; Lorentsen, Svein‐Håkon; Mallory, Mark L.; Robertson, Gregory J.; et al.
Abstract: The timing of annual events such as reproduction is a critical component of how free‐living organisms respond to ongoing climate change. This may be especially true in the Arctic, which is disproportionally impacted by climate warming. Here, we show that Arctic seabirds responded to climate change by moving the start of their reproduction earlier, coincident with an advancing onset of spring and that their response is phylogenetically and spatially structured. The phylogenetic signal is likely driven by seabird foraging behavior. Surface‐feeding species advanced their reproduction in the last 35 years while diving species showed remarkably stable breeding timing. The earlier reproduction for Arctic surface‐feeding birds was significant in the Pacific only, where spring advancement was most pronounced. In both the Atlantic and Pacific, seabirds with a long breeding season showed a greater response to the advancement of spring than seabirds with a short breeding season. Our results emphasize that spatial variation, phylogeny, and life history are important considerations in seabird phenological response to climate change and highlight the key role played by the species' foraging behavior. Abstract : The timing of reproduction is a critical component of how free‐living organisms respond to ongoing climate change, especially in the Arctic, which is disproportionally impacted by climate warming. Arctic seabirds respond to climate change by moving the start of their reproduction earlier, coincident with an advancing onset of spring, but their response is dependent on the ocean basin and foraging strategy. Surface‐feeding species advanced their reproduction in the last 35 years while diving species showed remarkably stable breeding timing. The earlier reproduction for Arctic surface‐feeding birds was significant in the Pacific only, where the spring advancement was most pronounced.